COVID-19 and Global Poverty: Are LDCs Being Left Behind? - Valensisi, Giovanni (Eur J Dev Res, 2020)
The paper provides a preliminary assessment of COVID-19’s impact on global poverty in the light of IMF’s growth forecasts. It shows that the pandemic will erode many of the gains recorded over the last decade in terms of poverty reduction. Our baseline case suggests that globally the number of people living below US$1.90 per day will increase by 68 million in 2020 alone; this rise could however approach 100 million, should the recession turn out to be more severe than initially expected, as many practitioners fear. Without effective international support, this setback will pose a critical threat to the achievement of the United Nations 2030 Agenda for Sustainable Development. The fallout from the pandemic will also exacerbate the geographic concentration of poverty, to the extent that the Least Developed Countries, with only 14% of the global population, are set to represent the main locus of extreme poverty worldwide.